DEMONSTRATION AND METHOD FOR CALCULATING THE EFFICIENCY OF DIFFERENTIAL MECHANISM - Barbu PLOSCEANU; Ovidiu VASILE (Fiabilitate şi Durabilitate)
To solve the problem of calculating the power circulation and efficiency, the mechanical transmission cycles are reform the notion of efficiency. Using the principle of virtual velocities presented a demonstration to calculate power flux indicator. Finally, examples of the method for calculation of differential type mechanisms.